1978
DOI: 10.1016/0043-1648(78)90124-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of formation of polymeric transfer films

Abstract: The role of the transfer film in reducing wear of polymers is discussed. It is shown that the transfer film forms more readily on roughened surfaces and that it can exist in a solid state and in a low viscosity or fluid state. Each state controls friction and wear of the polymer in a different way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 2 publications
0
30
0
1
Order By: Relevance
“…Extrapolation of friction coefficients reveals zero friction at temperatures above 200°C, corresponding to a degradation temperature of e.g. 220°C as reported by Rhee and Ludema [43]. The hypothetical formation of a supplementary crystalline structure with high temperature resistance due to orientation effects should then explain this high-temperature behaviour, however, this should be ascertained by further research in the second part of this project.…”
Section: Influence Of Temperature On Frictionmentioning
confidence: 81%
“…Extrapolation of friction coefficients reveals zero friction at temperatures above 200°C, corresponding to a degradation temperature of e.g. 220°C as reported by Rhee and Ludema [43]. The hypothetical formation of a supplementary crystalline structure with high temperature resistance due to orientation effects should then explain this high-temperature behaviour, however, this should be ascertained by further research in the second part of this project.…”
Section: Influence Of Temperature On Frictionmentioning
confidence: 81%
“…Some reactions are controlled by radical formation. Rhee et al [87] reported that the friction and wear processes at high temperatures are rather controlled by pyrolysis. Thermal and oxidative reactions cause degraded wear particles to incorporate in the transfer film and change its stability.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…To give a perspective on the tenacity of oxides, some tests were done by sliding various polymers over 440C stainless steel. It was found that the polymers that had a shear strength less than 9200 lbf in-* (63.4 MPa) did not remove oxide from the stainless steel, whereas polymers with a shear strength over 9500 lbf in-* (65.5 MPa) did remove oxide from stainless steel [64]. It would, therefore, seem that the tenacity or shear strength of oxide on stainless steel is of the order of 9500 lbf in-* (65.5 MPa) and perhaps this property should be the focus of research attention rather than the properties of the substrates.…”
Section: Research Topics On Oxidesmentioning
confidence: 99%
“…asperity height, skewness, kurtosis and bearing area. It is interesting to see how often the surface finish (or roughness) is specified numerically in the geometric progression 1, 2, 4, 8, 16,32,64 etc. It would appear that specification in intermediate numbers is either unnecessary, or perhaps designers do not really know what roughness is needed.…”
Section: Effect Of Surface Finishmentioning
confidence: 99%